Hypoxia‐inducible factor 2α is a novel inhibitor of chondrocyte maturation. Issue 10 (21st March 2021) - Che, Xiangguo; Park, Na‐Rae; Jin, Xian; Jung, Youn‐Kwan; Han, Min‐Su; Park, Clara Yongjoo; Chun, Jang‐Soo; Kim, Seong‐Gon; Jin, Jingchun; Kim, Hyun‐Ju; Lian, Jane B.; Stein, Janet L.; et al.
Abstract: Hypoxic environment is essential for chondrocyte maturation and longitudinal bone growth. Although hypoxia‐inducible factor 1 alpha (Hif‐1α) has been known as a key player for chondrocyte survival and function, the function of Hif‐2α in cartilage is mechanistically and clinically relevant but remains unknown. Here we demonstrated that Hif‐2α was a novel inhibitor of chondrocyte maturation through downregulation of Runx2 stability. Mechanistically, Hif‐2α binding to Runx2 inhibited chondrocyte maturation by Runx2 degradation through disrupting Runx2/Cbfβ complex formation. The Hif‐2α‐mediated‐Runx2 degradation could be rescued by Cbfβ transfection due to the increase of Runx2/Cbfβ complex formation. Consistently, mesenchymal cells derived from Hif‐2α heterozygous mice were more rapidly differentiated into hypertrophic chondrocytes than those of wild‐type mice in a micromass culture system. Collectively, these findings demonstrate that Hif‐2α is a novel inhibitor for chondrocyte maturation by disrupting Runx2/Cbfβ complex formation and consequential regulatory activity.